Relationship between expression of HBV-infection markers in placenta and clinical data of mothers and their newborns - M. A. Belopolskaya; V. E. Karev; V. Yu. Avrutin; A. V. Dmitriev; D. A. Gusev (Журнал инфектологии)
Vertical transmission of viral hepatitis B (HBV) is one of the main transmission ways in endemic regions. There is a relationship between structural changes in the placenta and the clinical course of HBV infection. The risk of vertical transmission of hepatitis B depends on the condition of the placenta.The goal of this work was to study the relationship between HBsAg and / or HBcorAg expression in placenta on the one hand, and clinical parameters of mothers and newborns on the other hand.The study included 19 patients with CHB who gave birth at the Botkins infectious disease hospital in 2019. The first group included patients with markers of HBV infection (HBsAg and / or HBcorAg) detectable via immunohistochemical examination in at least one of the layers of the placenta. In patients from the second group, no markers of HBV infection were detected in any layer of the placenta. Inflammatory changes in placenta were detected in all women from the first group and in 9 (64%) women from the second group. HBsAg in umbilical cord blood was detected in 3 (16%) newborns. In two patients, whose children had HBsAg in the umbilical cord blood, no markers of HBV infection were detected in placenta. In the first group, only one newborn had HBsAg in umbilical cord blood. In two patients receiving an antiviral treatment during pregnancy, markers of HBV infection were identified in the placenta. Markers of HBV infection in placenta were also detected in women with undetectable viral load.ConclusionsMarkers of HBV infection can be found in placenta at low maternal viral load.HBsAg in umbilical cord blood can be detected even in patients with no markers of HBV infection in placenta.Antiviral treatment during pregnancy does not prevent the possibility of placenta’s infection with HBV.